ANALISIS RUAS SUNGAI CILIWUNG HILIR TERHADAP DEBIT BANJIR DI DKI JAKARTA MENGGUNAKAN HEC – RAS - Fathurrahman; Darmadi (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
The area of DKI Jakarta has an area of ± 661.52 Km2, the City of DKI Jakarta is a swamp managed by 13 water channels that flow to the north of the island of Java, the development of water in DKI Jakarta is part of the way it is released into the sea by gravity and partly by the system. pump. Floods that occur every year in DKI Jakarta cannot be separated from the impact of the flow of water that crosses it. Very large waterways start in the southern part of DKI Jakarta, especially the Bogor area which has a height of more than 200 m above sea level and high rainfall, so DKI Jakarta is usually an area that collects water from its upstream river. The purpose of discussing this problem is to find out the amount of river flood discharge, find out whether the capacity of the river is able to accommodate flood discharge, find out how many pumps and how much pump capacity is needed in order to overcome flood discharge in the marina watershed. Thus, the conclusions obtained from the modeling results of the existing condition of the river's capacity are not able to accommodate flood discharge, therefore it is necessary to install a pump to cope with flooding in the DKI Jakarta Marina watershed using the Hec - Ras method.